(untitled) (Research, Society and Development, 2021)
Odontogenic infections are commonly found in the oral and maxillofacial region, therefore, the correct management of this condition becomes an essential condition for maxillofacial surgeons. This study aims to point out complex infections arising from odontogenic sources, analyzing the concept, diagnosis and form of appropriate treatment in order to contribute to a better evolution of the clinical picture. A literature review was carried out through the crossing of selected descriptors in electronic search between the years 2006 and 2021, found in the journals of the SCIELO, LILACS and MEDLINE databases. Among the complex infections of odontogenic origin, one can mention Ludwig’s Angina, Septic Cavernous Sinus Thrombrosis, Necrotizing Descending Mediastinitis, Odontogenic Sinusitis, Cerebral Abscess and Necrotizing Fasciitis. Although they are all complications in the face of infection and similar symptoms, each one has peculiar characteristics where it is possible to differentiate between them. The approach adopted in the face of these infections is a primordial factor for the success of the treatment. Conclusion: Knowledge of anatomical areas as well as professional training in prevention, diagnosis and, above all, in clinical resolution, is essential to alleviate the severity of these infections.